2015
DOI: 10.1097/igc.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Double Docking to Improve Lymph Node Dissection: When Robotically Assisted Laparoscopy for Para-aortic Lymphadenectomy Is Associated to a Pelvic Procedure

Abstract: We compare 2 techniques to realize robotic assisted para-aortic lymphadenectomy combined with pelvic procedure. Double docking seems to improve histological results compared to single docking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In our opinion this is adequate, considering that other studies on robotic infrarenal paraaortic LND in EC or different gynecological malignancies with 5-97 patients report a mean number of 13-31.6 retrieved pelvic and 4.5-25.5 paraaortic lymph nodes (13,(19)(20)(21)(22)(23). In a retrospective study in 41 patients in which it is unclear whether an intention-to-treat policy was applied, Frank e observed that double docking was favorable for infrarenal LND, but with the double docking procedure the a lymph node count was comparable to our single docking procedure in spite of the operative time being 126 min longer (24). In traditional laparoscopy, a lymph node yield of 17.4-22 pelvic and 2.5-12 paraaortic nodes has been reported (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 84%
“…In our opinion this is adequate, considering that other studies on robotic infrarenal paraaortic LND in EC or different gynecological malignancies with 5-97 patients report a mean number of 13-31.6 retrieved pelvic and 4.5-25.5 paraaortic lymph nodes (13,(19)(20)(21)(22)(23). In a retrospective study in 41 patients in which it is unclear whether an intention-to-treat policy was applied, Frank e observed that double docking was favorable for infrarenal LND, but with the double docking procedure the a lymph node count was comparable to our single docking procedure in spite of the operative time being 126 min longer (24). In traditional laparoscopy, a lymph node yield of 17.4-22 pelvic and 2.5-12 paraaortic nodes has been reported (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, this represents one of the largest series analyzing surgical outcomes and postoperative morbidity of robotic transperitoneal surgery for staging in gynecological cancer patients undergoing aortic lymphadenectomy 25,28,29,[32][33][34][35][36][37] (Table 5). Systematic aortic lymphadenectomy was performed in all cases using a single-docking approach.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of robotic technology that facilitate surgical performances also help to shorten the learning curve, including three‐dimensional visualization, articulated instrumentation, and stability of the camera . In addition, further technological improvements have improved the versatility of its use, and robotic‐assisted laparoscopy is now a valid and diffused surgical method for treatment of gynecological cancers, even when para‐aortic lymphadenectomy is required …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para-aortic lymphadenectomy (PAL) is an important step in the surgical staging of a variety of gynecologic malignancies, such as cervical, endometrial, and ovarian cancers ( 1 3 ). It may provide significant information on the spread of cancer and the prognosis, and help in developing targeted primary and adjuvant therapy ( 4 ).…”
Section: Introductionmentioning
confidence: 99%